The Practice of Enterprise Modeling : 8th IFIP WG 8.1. Working Conference, PoEM 2015, Valencia, Spain, November 10-12, 2015, proceedings /: 8th IFIP WG 8.1. Working Conference, PoEM 2015, Valencia, Spain, November 10-12, 2015, proceedings. (2015) - Unknown
No abstract available